Holy men, holy women a journey into the faiths of Malaysians and other essays - Dina Zaman 1969- (Strategic Information and Research Development Centre, 2018)
Needing a break from her first book, I Am Muslim, Dina Zaman embarked on a two-year journey around Malaysia - the length of the peninsula as well as Sabah and Sarawak. She met people of many faiths. And from these encounters she has woven together a tapestry of vital stories: of nuns and shamans, of silat practitioners who she inadvertently offended, of pilgrims and ustaz, of hijabis who pole dance, and she ended up in Memali to discover that tragic tale. This collection of essays - animated, engaging and provocative - opens a window on the sometimes troubled terrain of religious beliefs and practices. The accounts are personal and intimate, and at the same time throw light on some of the most pressing issues that confront society today: mindfulness and worldliness, interfaith relations and lifestyle choices, class and conviction, identity and religiosity. This is Malaysia, peopled by holy men and holy women of all stripes, and Dina Zaman is your compelling guide.